COMPARATIVE ANALYSIS OF THE USE OF YAHOO AND GOOGLE INFORMATION SYSTEMS IN THE ENVIRONMENT OF AMBON STATE POLYTECHNIC LECTURERS AND STUDENTS - FEBIYOLA WIJAYA; VASCOLINO PATTIPEILOHY (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
Google is indeed a brand in information systems, especially in search engines, popular among lecturers and students of the Ambon State Polytechnic compared to Yahoo. The analysis technique used is qualitative analysis which describes the theoretical approach from the opinions of experts about the quality of information systems and quantitative analysis where data processing is a process to obtain data from each research variable that is ready to be analyzed. Data processing includes data editing, data transformation (coding), data tabulation and data presentation in order to obtain complete data from each object for each variable studied. Google has an advantage over Yahoo, at all levels of information system quality.